(untitled) (The Journal of Psychology and Sociology, 2012)
In this article the educational system of Republic of Kazakhstan and a level of development of professional education are considered. Also in article a question of sights, demands are considered and about turning on professional education on a global scale are considered. The author gives the generalized characteristic to professional education stating economic system of our country.